Adipokinetic hormone counteracts oxidative stress elicited in insects by hydrogen peroxide: in vivo and in vitro study - Bednářová, Andrea (Jihočeská univerzita, 2013)
The involvement of members of Adipokinetic hormone (AKH) family in regulation of response to oxidative stress (OS) was investigated in the present study. OS was elicited in the insect body by exogenous application of hydrogen peroxide. In vivo experiments reveal that injection of hydrogen peroxide into the haemocoel of the firebug, Pyrrhocoris apterus, increases the level of AKH in the central nervous system (CNS) and in the haemolymph. The injection of hydrogen peroxide also increases the mortality of experimental bugs, whereas co-injection of hydrogen peroxide with Pyrap-AKH reduces mortality to control levels. Importantly, an increase in haemolymph protein carbonyl (an OS biomarker) levels is decreased to control levels when hydrogen peroxide is co-injected with Pyrap-AKH. Similar results were obtained using in vitro experiments. OS biomarkers such as malondialdehyde and protein carbonyls were significantly enhanced upon exposure of isolated CNS to hydrogen peroxide in vitro, whereas co-treatment of the CNS with hydrogen peroxide and Pyrap-AKH reduces their level significantly. Catalase activity was measured as well and the same pattern was observed. The results of the present study provide strong support on the feedback regulation between oxidative stressors and AKH action, and implicate AKH in counteracting OS.
Adipokinetic hormone counteracts oxidative stress elicited in insects by hydrogen peroxide: in vivo and in vitro study
Adipokinetic hormone counteracts oxidative stress elicited in insects by hydrogen peroxide: in vivo and in vitro study
Keywords: Adipokinetic hormone; catalase; ELISA; hydrogen peroxide; malondialdehyde; oxidative stress; protein carbonyls; Adipokinetic hormone; catalase; ELISA; hydrogen peroxide; malondialdehyde; oxidative stress; protein carbonyls